Thalamic Atrophy Plays a Crucial Role in the Effect of Asymptomatic Carotid Stenosis on Cognitive Impairment - Zhang W (Dove Medical Press, 2020)
Wen Zhang,1 Zhao Qing,1 Yongwei Hu,2 Mingran Shao,1 Jiaming Lu,1 Junxia Wang,1 Ming Li,1 Xin Zhang,1 Zuzana Nedelska,3 Jakub Hort,3 Zhishun Wang,4 Tong Qiao,5 Bing Zhang1 1Department of Radiology, Drum Tower Hospital, The Affiliated Hospital of Nanjing University Medical School, Nanjing, People’s Republic of China; 2Department of Vascular and Interventional Radiology, Wujin People’s Hospital Affiliated to Jiangsu University, Changzhou, People’s Republic of China; 3Department of Neurology, Memory Clinic, 2nd Faculty of Medicine, Charles University and Motol University Hospital, Prague, Czech Republic; 4Columbia University Vagelos College of Physicians and Surgeons, New York, NY, USA; 5Department of Vascular Surgery, Drum Tower Hospital, The Affiliated Hospital of Nanjing University Medical School, Nanjing, People’s Republic of ChinaCorrespondence: Bing ZhangDepartment of Radiology, Drum Tower Hospital, The Affiliated Hospital of Nanjing University Medical School, No. 321 Zhongshan Road, Nanjing 210008, People’s Republic of ChinaTel +86 15851803070Email zhangbing_nanjing@nju.edu.cnTong QiaoDepartment of Vascular Surgery, Drum Tower Hospital, The Affiliated Hospital of Nanjing University Medical School, No. 321 Zhongshan Road, Nanjing 210008, People’s Republic of ChinaTel +86 15951985338Email qiaotongmail@aliyun.comPurpose: Our objectives were to assess the abnormalities of subcortical nuclei by combining volume and shape analyses and potential association with cognitive impairment.Patients and Methods: Twenty-nine patients with severe ACS of the unilateral internal carotid artery and 31 controls were enrolled between January 2017 to August 2018. All participants underwent a comprehensive neuropsychological evaluation, blood lipid biochemical measurements, and structural magnetic resonance imaging (MRI) to measure subcortical volumes and sub-regional shape deformations. Basic statistics, correction for multiple comparisons. Seventeen ACS patients underwent carotid endarterectomy (CEA) within one week after baseline measurements, cognitive assessments and MRI scans were repeated 6 months after CEA.Results: The ACS patients had higher apolipoprotein B/apolipoprotein A1 (ApoB/ApoA1) ratio and worse performance in all cognitive domains than controls. Moreover, the ACS patients showed more profound thalamic atrophy assessed by shape and volume analysis, especially in the medial dorsal thalamus. No significant differences were found in other subcortical nuclei after multiple comparisons correction. At baseline, thalamic atrophy correlated with cognitive impairment and ApoB/ApoA1 ratio. Furthermore, mediation analysis at baseline showed that the association of carotid intima-media thickness with executive functioning was mediated by thalamic volume. After CEA, cognitive improvement and increase in the bilateral medial dorsal thalamic volume were observed.Conclusion: Our study identified the distinct atrophy of subcortical nuclei and their association with cognition in patients with ACS. Assessments of the thalamus by volumetric and shape analysis may provide an early marker for cerebral ischemia and reperfusion after CEA.Keywords: asymptomatic carotid stenosis, cognitive impairment, magnetic resonance imaging, endarterectomy, thalamus